Early versus later initiation of parenteral nutrition for very preterm infants: a propensity score-matched observational study. Issue 2 (18th November 2021) - Uthaya, Sabita; Longford, Nicholas; Battersby, Cheryl; Oughham, Kayleigh; Lanoue, Julia; Modi, Neena
Abstract : Objective: To evaluate the impact of timing of initiation of parenteral nutrition (PN) after birth in very preterm infants. Design: Propensity-matched analysis of data from the UK National Neonatal Research Database. Patients: 65 033 babies <31 weeks gestation admitted to neonatal units in England and Wales between 2008 and 2019. Interventions: PN initiated in the first 2 days (early) versus after the second postnatal day (late). Babies who died in the first 2 days without receiving PN were analysed as 'late'. Main outcome measures: The main outcome measure was morbidity-free survival to discharge. The secondary outcomes were survival to discharge, growth and other core neonatal outcomes. Findings: No difference was found in the primary outcome (absolute rate difference (ARD) between early and late 0.50%, 95% CI −0.45 to 1.45, p=0.29). The early group had higher rates of survival to discharge (ARD 3.3%, 95% CI 2.7 to 3.8, p<0.001), late-onset sepsis (ARD 0.84%, 95% CI 0.48 to 1.2, p<0.001), bronchopulmonary dysplasia (ARD 1.24%, 95% CI 0.30 to 2.17, p=0.01), treated retinopathy of prematurity (ARD 0.50%, 95% CI 0.17 to 0.84, p<0.001), surgical procedures (ARD 0.80%, 95% CI 0.20 to 1.40, p=0.01) and greater drop in weight z-score between birth and discharge (absolute difference 0.019, 95% CI 0.003 to 0.035, p=0.02). Of 4.9% of babies who died in the first 2 days, 3.4% were in the late group and not exposed to PN. Conclusions: Residual confounding and survival bias cannot be excluded and justify the need for a randomised controlled trial powered to detect differences in important functional outcomes. Abstract : This large observational study of over 65, 000 infants uses propensity matching to assess the impact of early (<2 days of age) and late (>2 days) commencement of parenteral nutrition in preterm infants born before 31 weeks gestation.